Pengaruh Struktur Iklan Two Sided, Pengetahuan dan Preferensi untuk Produk Rokok terhadap Minat Beli - Susianti Susianti; Samron Akhiri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
Looking at cigarette product advertisements in various media, there is always a warning about the dangers of smoking to health in addition to information about the product itself. This study aims to identify the level of awareness and knowledge of consumers among smoker employees of PT. TEL Pulp and Paper on the influence of cigarettes on health, then continued by identifying the influence of cigarette advertisement structure on buying preferences, preferences and interests, and identifying whether there are significant differences in the assessment of advertising structure, level of awareness and knowledge, likes and preferences and beliefs and purchases between smokers based on differences in the number of cigarettes consumed per day. Hypothesis testing will be done by the Simple Linear Regression method. The results of the study show that From the output of the summary model, the determination table above gives R Square of 0.824. This shows that the Two Sided Advertisements variable and knowledge and awareness simultaneously have an influence of 0.824 or 82.4% on buying interest, while the remaining 17.6% is the influence of (aspects) or other factors not included in the study this is like preferences and preferences etc. While the correlation value (R) = 0.769. This shows that the Two Sided Advertisements variable and knowledge and awareness, the correlation is very strong against buying interest. Keywords: Two-Sided Ad Structure, Awareness, Knowledge, Preference